2020
DOI: 10.1021/acs.biomac.0c00170
|View full text |Cite
|
Sign up to set email alerts
|

Colorless Silk/Copper Sulfide Hybrid Fiber and Fabric with Spontaneous Heating Property under Sunlight

Abstract: With the increasing demand for comfort, thinness, and warmth of fabrics, various functional fibers have emerged. However, natural silkworm silk, as one of the most widely used natural fibers in textile, faces the issue that it cannot be modified during the spinning process like synthetic fibers. Herein, copper sulfide nanoparticles (CuS NPs) with a near-infrared (NIR) absorption property were first prepared by using regenerated silk fibroin (RSF) as the biological template. Then, trace CuS NPs prepared in RSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The degumming process of B. mori silk cocoons was conducted following a well-established procedure that has been reported in our previous work . In brief, raw cocoons were twice treated in a boiling aqueous solution of 0.5 wt % NaHCO 3 for 30 min and then rinsed thoroughly with deionized water before being air-dried at 40 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degumming process of B. mori silk cocoons was conducted following a well-established procedure that has been reported in our previous work . In brief, raw cocoons were twice treated in a boiling aqueous solution of 0.5 wt % NaHCO 3 for 30 min and then rinsed thoroughly with deionized water before being air-dried at 40 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The degumming process of B. mori silk cocoons was conducted following a well-established procedure that has been reported in our previous work. 50 In brief, raw cocoons were twice treated in a boiling aqueous solution of 0.5 wt % NaHCO 3 for 30 min and then rinsed thoroughly with deionized water before being air-dried at 40 °C overnight. The degummed silk fibers were dissolved in FA with CaCl 2 at room temperature for 3 h. After defoaming, a transparent homogeneous solution was poured into Teflon molds, which then immersed in deionized water to form RSF hydrogels.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Silk, also known as natural silk, is a continuous long fiber formed by the solidification of silk liquid secreted by mature silkworms during cocooning. The silk fiber (SF) is a protein fiber, containing 18 kinds of amino acids, which is similar to the structure of human skin, so it is commonly known as the “second skin” and the “fiber queen.” 1,2 Silk generally includes mulberry silk (silkworm silk), tussah silk, castor silk, and so forth. Each fiber of silk consists of a core fiber made up of two strands of silk fibroin fibers and an outer layer of sericin 3,4 which plays a bonding role.…”
Section: Introductionmentioning
confidence: 99%
“…BSA-Au NCs showed no significant negative effect on silkworm when the dose of Au was below 9.38 µg/silkworm (about 6.25 mg/kg). In a previous study, functional nanoparticles were directly blended into the spinning solution and RSF fibers were prepared by wet spinning technology which can functionalize RSF fibers and maintain the high strength of RSF fibers as well [19][20][21][22][23][24]. For example, Pham et al [25] reported a novel approach to toughen epoxy resin with nano-silica fabricated from rice husk using a thermal treatment method with a particle size distribution in a range of 40-80 nm.…”
Section: Introductionmentioning
confidence: 99%